1973
DOI: 10.1029/ja078i010p01615
|View full text |Cite
|
Sign up to set email alerts
|

Distributions and characteristics of high-latitude field-aligned electron precipitation

Abstract: Satellite measurements of field‐aligned auroral electron precipitation have been analyzed using 16 months of data from the Ogo 4 auroral particles experiment. As can be seen from the moving satellite, the anisotropies are of short duration and are most likely to occur when particle fluxes are high. Field‐aligned 2.3‐kev electron precipitation is found in an oval‐shaped region primarily in the nighttime hours; maximum probability is at ∼70° invariant latitude near midnight, congruent to and poleward of the auro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 29 publications
5
29
0
Order By: Relevance
“…The amplitude of the peaks has a minimum at 02-04 MLT which might indicate that the midnight peaks have a different source than the day peaks. It may also be pointed out that anisotropies at 2.3 keV electrons reported by Berko (1972) have a maximum occurrence at midnight and at 70-72° in invariant latitude and decrease towards dawn with very few cases found on the dayside, while anisotropies at 1.3 keV reported by Holmgren and Aparicio (1972) show a second maximum in the day. This indicates also that there are two different kinds of particle populations at these low energies in the latitude range where the 0.7 keV peaks are observed.…”
Section: Discussionmentioning
confidence: 85%
“…The amplitude of the peaks has a minimum at 02-04 MLT which might indicate that the midnight peaks have a different source than the day peaks. It may also be pointed out that anisotropies at 2.3 keV electrons reported by Berko (1972) have a maximum occurrence at midnight and at 70-72° in invariant latitude and decrease towards dawn with very few cases found on the dayside, while anisotropies at 1.3 keV reported by Holmgren and Aparicio (1972) show a second maximum in the day. This indicates also that there are two different kinds of particle populations at these low energies in the latitude range where the 0.7 keV peaks are observed.…”
Section: Discussionmentioning
confidence: 85%
“…According to the statistics of the S3-3 data in the auroral oval, the field-aligned electrons were considered to be stable in a circumpolar zone (Collin et al, 1982). Berko (1973) studied the field-aligned electron precipitation that was most likely to occur when particle fluxes were high. He also noticed that the field-aligned precipitation generally was a short-time duration phenomenon, rarely appearing continuously for more than 5 to 10 s according to the data from the OGO 4 satellite at an altitude of 412-908 km.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing the OGO 4 satellite data at altitudes of 412-908 km, Berko (1973) pointed out that the FAEs were distributed over the entire auroral oval with a maximum occurrence at about ILAT (invariant latitude) 70°-72.5°in the range of magnetic local time (MLT) 2200-0100(+1). Using S3-3 data obtained at low altitude (3,000-8,000 km) in the northern polar region, Collin et al (1982) have shown that the FAEs were limited to an ILAT range within 63-81°, and the MLT distribution was double peaked in the morning and evening at MLT 0700 and 2200, respectively, and only in the northern polar region.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution and spectral characteristics of 2.3 keV field-aligned electrons have been presented in a statistical study by Berko (1973).…”
Section: Introductionmentioning
confidence: 99%